PWE-077 Residual Intestinal Metaplasia after Successful Endoscopic Therapy for Barrett's Related Neoplasia Confers Higher Long Term Risk for Disease Recurrence, on Behalf of The UK RFA Registry. (17th August 2016) - Lipman, G; Gupta, A; Dunn, JM; Morris, D; Smart, H; Bhandari, P; Willert, RP; Fullarton, G; Morris, AJ; Di Pietro, M; Gordon, C; Penman, I; et al.
Abstract : Introduction: Endoscopic resection (ER) followed by Radiofrequency ablation (RFA) is the first line treatment for neoplastic Barrett's oesophagus (BE). Metachronous neoplasia after focal eradication of disease is ~20%. We examine data from the UK registry of 28 centres to establish if residual metaplastic BE carries a risk of disease recurrence. Methods: Visible lesions were removed by EMR. Patients then underwent RFA 3 monthly. Biopsies were taken at 12 months to assess treatment success with repeat biopsies every 6–12 months thereafter. Dysplasia recurrence was compared in patients who had complete reversal of BE and neoplasia (CR-IM) to those in whom dysplasia alone was eradicated (CR-D only). Residual BE was confirmed with visible columnar epithelium proximal to the OGJ with biopsies showing IM. Results: 517 patients achieved CR-IM & 96 patients achieved CR-D only after 12 months treatment . Sex & ER rates were not significantly different between groups. The CR-D only group were older (mean age 70 vs 67, p < 0.01) and had longer initial BE (mean length 6.2 cm vs 4.7 cm, p < 0.0001). Mean residual BE length was 1.4 cm. At median follow up 32 months, more patients were disease free in the CR-IM group (96% vs 89%) and Kaplan Meier statistics demonstrated an improved predicted 6 year neoplasia free survival in the CR-IM group (90% vs 84% log rank p 0.0015). Most recurrences occurred within 3 years of follow up. Conclusion: Endotherapy should aim to clear neoplasia and underlying metaplastic BE to improve long term outcome. Patients with CR-D but not CR-IM at the end of treatment have an increased risk of neoplasia recurrence. This may have implications for post treatment surveillance intervals. Disclosure of Interest: None Declared